Analysis of Cytokinin Metabolism in ipt Transgenic Tobacco by Liquid Chromatography-Tandem Mass Spectrometry. - Redig, P. (1996)
The endogenous levels of the major, naturally occurring cytokinins in Pisum sativum ribulose-1,5-bisphosphate carboxylase small subunit promoter-isopentenyl transferase gene (Pssu-ipt)-transformed tobacco (Nicotiana tabacum L.) callus were quantified using electrospray-liquid chromatography-tandem mass spectrometry during a 6-week subcultivation period. An ipt gene was expressed under control of a tetracycline-inducible promoter for a more detailed study of cytokinin accumulation and metabolism. Activation of the ipt in both expression systems resulted in the production of mainly zeatin-type cytokinins. No accumulation of isopentenyladenine or isopentenyladenosine was observed. In Pssu-ipt-transformed calli, as well as in the tetracycline-inducible ipt leaves, metabolic inactivation occurred through O-glucoside conjugation. No significant elevation of cytokinin N-glucosides levels was observed. Side-chain reduction to dihydrozeatin-type cytokinins was observed in both systems. The levels of the endogenous cytokinins varied in time and were subject to homeostatic regulatory mechanisms. Feeding experiments of ipt transgenic callus with [3H]isopentenyladenine and [3H]isopentenyladenosine mainly led to labeled adenine-like compounds, which are degradation products from cytokininoxidase activity. Incorporation of radioactivity in zeatin riboside was observed, although to a much lesser extent.